BOEKHANDEL TAN KHOEN SWIE KEDIRI: THE AGENT OF JAVANESE CULTURE - Wisnu Wisnu (Paramita: Historical Studies Journal)
This paper reveals the way Boekhandel Tan Khoen Swie Kediri, as an agent of Javanese culture, run his publishing house during amidst both the colonial government and Indonesian government, spreading Javanese culture to the society in Java and throughout Indonesia. The history of this publishing house is interesting in which it is interrelated with three different policies from three different types of government ideology. This research which means searching, criticizing, interpreting, and arranging the sources in the form of historical writing. This research also applied Gidden’s theory of structuration to clarify the position of Tan Khoen as a publishing agent. The discussion on the structure of the literary society, which consisted of the representatives from the government, authors, publishers, and readers becomes an integral part of the study. This study concludes both the government and private publishers had an intention to educate people although Tan Khoen Swie did not tied its theme on the existing system. However structurally, the existence Boekhandel Tan Khoen Swie were bounded by the authors, other publishers, and readers. The seasons for publishing Javanese culture books because the books contained noble culture, which needs to be disseminated, the legitimation of Javanese writers, and promising market prospect. The success of Tan Khoen Swie business lies in its ability to build networking among authors, publishers, and readers or bookstores. The books published in his business spread across Indonesia. He served both as a cultural broker and as an agent of Javanese culture.